2021
DOI: 10.1159/000521364
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anesthesia versus General Anesthesia in Gynecological Laparoscopic Surgery: A Systematic Review and Meta-Analysis

Abstract: Introduction: In the last years, spinal anesthesia (SA) has emerging as alternative to general anesthesia (GA) for the laparoscopic treatment of gynecological diseases, for better control of postoperative pain. The aim of the review is to compare the advantages of SA compared to GA. Methods: MEDLINE, Scopus, ClinicalTrials.gov, EMBASE, Cochrane Library, and CINAHL were searched from inception until March 2021. Randomized controlled trials (RCTs) and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…Our data confirm the suitability of laparoscopy surgery under RA for gynecological surgery, a still debated subject in literature, in contrast to general surgery of which successful results are already reported in literature [ 14 18 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data confirm the suitability of laparoscopy surgery under RA for gynecological surgery, a still debated subject in literature, in contrast to general surgery of which successful results are already reported in literature [ 14 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…Only one case report on total laparoscopic hysterectomy is reported in the literature [ 13 ]. Recently, a review by Della Corte et al has shown no significant advantages to using SA over GA for laparoscopic treatment of gynecological diseases [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were comparable to the previous studies. [10,11]Among both groups paratubal cystectomy was most common symptom found in 6 (13.3%) cases and 7 (15.6%) cases. Mean operative time in neuroaxial group was lower 45.3±6.52 minutes as compared to group II was 54.8±11.42 minutes.…”
Section: Discussionmentioning
confidence: 94%
“…The results of this case series provide the indication that RA could be considered a valid alternative to GA, not only for minimally invasive and short-term gynecological procedures [ 31 ], but even for longer and more complex gynecological surgery such as hysterectomy procedure. This represents a convincing result, especially if it is considered that a recent review with meta-analysis has demonstrated no significant advantages to using SA over GA for laparoscopic treatment of benign gynecological diseases [ 32 ]. On the other hand, a prospective study published by the same Group has reported how RA could be a viable option for well-selected patients affected by benign gynecological diseases [ 33 ].…”
Section: Discussionmentioning
confidence: 99%